Cone beam computed tomography-based models versus multislice spiral computed tomography-based models for assessing condylar morphology - Gomes, Liliane Rosas [UNESP]; Gomes, Marcelo Regis; Gonçalves, João Roberto [UNESP]; Ruellas, Antônio Carlos O.; Wolford, Larry M.; Paniagua, Beatriz; Benavides, Erika; Soares Cevidanes, Lúcia Helena (Elsevier, 2016)
Objective To quantitatively compare condylar morphology using cone beam computed tomography (CBCT) and multislice spiral computed tomography (MSCT) virtual three-dimensional surface models. Study Design The sample consisted of secondary data analyses of CBCT and MSCT scans obtained for clinical purposes from 74 patients treated with condylar resection and prosthetic joint replacement. Three-dimensional surface models of 146 condyles were constructed from each scan modality. Across-subject models were approximated and voxel-based registration was performed between homologous CBCT and MSCT images, making it possible to create average CBCT- and MSCT-based condylar models. SPHARM-PDM software provided matching points on each corresponding model. ShapeAnalysisMANCOVA software assessed statistically significant differences between observers and imaging modalities. One-sample t-tests evaluated the null hypothesis that the mean differences between each CBCT- and MSCT-based model were not clinically significant (<.5 mm). Tests were conducted at a significance level of P <.05. Results ShapeAnalysisMANCOVA showed no statistically significant difference between the average CBCT- and MSCT-based models (P >.68). During pairwise comparison, the mean difference observed was.406 mm (SD,.173). One sample t-test showed that mean differences between each set of paired CBCT- and MSCT-based models were not clinically significant (P = .411). Conclusion Three-dimensional surface models constructed from CBCT images are comparable to those derived from MSCT scans and may be considered reliable tools for assessing condylar morphology.